Synergistic ferroptosis‐starvation therapy for bladder cancer based on hyaluronic acid modified metal-organic frameworks - Yu Wang; Kunfeng Xie; Wei Chen; Yunze Fang; Qixin Mo; Henghui Zhang; Xinlei Zhao; Dongqing Li; Wanlong Tan; Peng Zhao; Fei Li (Wiley, 2023)
Abstract Bladder cancer (BCa) is one of the most common malignancies of the urinary tract. Metastasis and recurrence of BCa are the leading causes of poor prognosis, and only a few patients can benefit from current first‐line treatments such as chemotherapy and immunotherapy. It is urgent to develop more effective therapeutic method with low side effects. Here, a cascade nanoreactor, ZIF‐8/PdCuAu/GOx@HA (ZPG@H), is proposed for starvation therapy and ferroptosis of BCa. The ZPG@H nanoreactor was constructed by co‐encapsulation of PdCuAu nanoparticles and glucose oxidase into zeolitic imidazolate framework‐8 (ZIF‐8) modified by hyaluronic acid. The vitro results indicated that ZPG@H enhanced intracellular reactive oxygen species levels and reduced mitochondrial depolarization in the tumor microenvironment. Therefore, the integrated advantages of starvation therapy and chemodynamic therapy endow ZPG@H with a perfect ferroptosis inducing ability. This effectiveness, combined with its excellent biocompatibility and biosafety, means that ZPG@H could make a critical contribution to the development of novel BCa treatments.